Entrepreneurial knowledge and motivation’s influence on entrepreneurial intentions: the role of entrepreneurial self-efficacy - Arpita GOYAL; Rai MANSI; Shubham PANDEY (Theoretical and Applied Economics, 2023)

(untitled)
This paper explores the mediating effect of entrepreneurial self-efficacy in the association between entrepreneurial knowledge, motivation, and intention in the Indian context. SEM is applied on a sample of 750 final year students from the undergraduate and post graduate management program of Rajasthan. The findings show significant and positive mediating effect of self-efficacy on the association among entrepreneurial knowledge and intentions. However, no such impact of entrepreneurial self-efficacy has been found in the linkage between entrepreneurial motivation and intentions. Thus, this study encourages universities to offer entrepreneurial training modules to boost their self-confidence and motivate them to have entrepreneurial intention.